2022
DOI: 10.6035/recerca.5798
|View full text |Cite
|
Sign up to set email alerts
|

Aportaciones críticas y despatologizantes en la evaluación psicológica de la diversidad de género

Abstract: El énfasis de la psicología en la vivencia individual ha generado prototipos idealizados sobre la identidad de género, promulgados a través de las herramientas tradicionales de evaluación psicológica. Las personas transgénero y género no-conforme se han visto presionadas a encajar en las concepciones binarias de dichas evaluaciones, hasta la reciente despatologización aprobada por la Organización Mundial de la Salud. En el presente trabajo teórico se examina cómo se fueron transformando los discursos sobre la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…What is more, even though initiatives seem to have been taken in order to include nonbinary or alternative gender identities and expressions, gender assessment procedures as such have remained intact, in the sense that comorbidity evaluations and reductionist gender role questionnaires resist change (Abiétar, 2019; Argyriou, 2022). Studies have revealed the connections between such parameters and the reification of the—by now largely questioned—wrong‐body narrative (Esteve Alguacil & Farnós Amorós, 2021).…”
Section: The Derogation Of the Lgbti Lawsmentioning
confidence: 99%
“…What is more, even though initiatives seem to have been taken in order to include nonbinary or alternative gender identities and expressions, gender assessment procedures as such have remained intact, in the sense that comorbidity evaluations and reductionist gender role questionnaires resist change (Abiétar, 2019; Argyriou, 2022). Studies have revealed the connections between such parameters and the reification of the—by now largely questioned—wrong‐body narrative (Esteve Alguacil & Farnós Amorós, 2021).…”
Section: The Derogation Of the Lgbti Lawsmentioning
confidence: 99%